Phimosis in hooded foreskin is a curious presentation in adolescents: case series - Carmine Noviello; Ilaria Cascone; Gaia De Francesco; Mercedes Romano; Mirko Bertozzi; Francesco Miele; Alfonso Papparella (La Pediatria Medica e Chirurgica)
Phimosis is a pathological condition in children and is easy to diagnose. In particular cases it can be associated with curious malformations of the foreskin. Four adolescents (aged from 9 to 13 years) presented at our attention because of a phimosis with hooded foreskin. Symptoms complained were: balanitis, urinary infection, preputial urinary retention, or psychological problems. One of the cases was asymptomatic. No other malformations were present. The surgical treatment was to remove the hooded foreskin and treat the ventral part of the skin of the penis to avoid abnormal curvatures. This type of malformation should be recognized and treated even if asymptomatic because it can create psychological problems in adolescence. The surgical treatment must prevent penile curvatures.